Effects of preorganization in the chelation of UO22+ by hydroxamate ligands: cyclic PIPO−vs. linear NMA−. (2nd March 2018) - Sornosa-Ten, Alejandra; Jewula, Pawel; Fodor, Tamas; Brandès, Stéphane; Sladkov, Vladimir; Rousselin, Yoann; Stern, Christine; Chambron, Jean-Claude; Meyer, Michel
Abstract : Thanks to preorganization, 1, 2-PIPOH, the six-membered ring cyclic hydroxamic acid, binds uranyl six times more strongly than its linear, methyl-substituted homolog (NMAH). Abstract : Many siderophores incorporate as bidentate chelating subunits linear and more seldomly cyclic hydroxamate groups. In this work, a comparative study of the uranyl binding properties in aqueous solution of two monohydroxamic acids, the prototypical linear N -methylacetohydroxamic acid (NMAH) and the cyclic analog 1-hydroxypiperidine-2-one (PIPOH), has been carried out. The complex [UO2 (PIPO)2 (H2 O)] crystallized from slightly acidic water solutions (pH < 5), and its molecular structure was determined by X-ray diffraction. The uranyl speciation in the presence of both ligands has been thoroughly investigated in a 0.1 M KNO3 medium at 298.2 K by the combined use of four complementary techniques, i.e., potentiometry, spectrophotometry, Raman spectroscopy, and affinity capillary electrophoresis. Preorganization of the hydroxamate ligand for chelation by incorporation into a cyclic structure, as in PIPO −, results in an increase of nearly one order of magnitude in the formation constants of the uranyl complexes of 1 : 1 and 1 : 2 metal/ligand stoichiometries.